إعداد وتصميم لوحة القيادة - بن عيسى، إلهام Bin Issa, Ilham (جامعة محمد خيضر بسكرة - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير - مخبر مالية، بنوك وإدارة الأعمال, 2021)
أن التسيير الجيد للمؤسسة يستدعي الإلمام بمختلف المعلومات عن موارد المؤسسة وسياساتها، وحتى تتمكن المؤسسة من أخذ نظرة شاملة عن وضعيتها، وتضمن متابعة الأنشطة والعمليات، ونجاعة أساليب التسيير فيها تبعا للنتائج المحققة بها يتم استخدام لوحة القيادة، ولذا كان لا بد أن يمر بناء لوحات القيادة بعدة مراحل منهجية صارمة، حيث أن دقة عملية البناء تدعم فعالية هاته الأداة في قياس سياسات وأهداف المؤسسة وتقييمها، كما لابد أن تتم تشغيلها بطريقة عرض مناسبة تتلاءم ومحتوى المعلومات المقدمة. يهدف هذا البحث إلى التعرف على أهمية لوحة القيادة، وتوضيح طرق بناء وتصميم لوحة القيادة، والتعرف على عوامل نحاج وحدود استعمالها، وقد تم التوصل في هذا البحث إلى أن تعميم استخدام لوحة القيادة داخل المؤسسة تضمن وصول أكبر قدر من المعلومات على أساس منهجية تدعم روح المبادرة، وأن صحة القرارات ترتبط بفعالية الأعداد والتصميم.
The good management of the organization requires knowledge of the various information about the resource of the foundation resources and policies; and so that the foundation can take a comprehensive view of its situation, and ensures follow-up activities and processes, and efficient methods of management according to the results archived using the dashboard, so it was therefore necessary for the construction of the dashboard in several stages of a strict methodology as the accuracy of the construction process supports the effectiveness of this tool in measuring and evaluating the policies and objectives of the organization, it must also be operated in an appropriate display manner that is appropriate to the content of the information provided. This research aims to identify the importance of the dashboard, clarify the methods of building and designing the dashboard, and identify the factors of success and limits of its use. It has been concluded in this research that the universal use of the dashboard within the organization ensures that the maximum amount of information is accessed based on a methodology that supports entrepreneurship, and that the validity of decisions is linked to the effectiveness of preparation and design
Keywords: لوحة القيادة -- التقنيات التصميمية -- المؤشرات القيادية -- المؤسسات الجزائرية